PEMODELAN KONTROL FREKUENSI BEBAN DAN STRATEGI PEMUTUSAN BEBAN PADA PEMBANGKIT LISTRIK TENAGA GAS - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2016)
In a power system, load always changes; power flows to the system will be vary too. In the event of two interconnected power generations trip one of its generators unit, there will be a change in frequency. A model is developed to simulate the trip events, a model that represents gas turbine generator, GAST is turbine model used to simulate unit's frequency response against load changes in the power system. Using SIMULINK, a simulation tool a model for multi area is made, First model aims to distinct the response using the primary governor controller and secondary controller PID. PID control provides better transient oscillation of frequency response. Tie line bias control is used to zero frequency deviation in steady state, The generator characteristics allows balanced load-sharing between the two control areas. An extreme power failure condition is simulated to see worst frequency deviation may possible to occur in power system, an extreme condition where the load increases exceeding the power system’s maximum capacity. Load shedding of significant load can be done to restore the system’s frequency back to its nominal and prevent system collapse.